The Art of Questioning in Online Learning: Effective Questioning Strategies in EFL Reading Class - Siti Yulidhar Harunasari; Soepriyatna Soepriyatna; Nita Fitriani; Ellen Juita Gultom (International Journal of Research in Education, 2023)
The advent of online learning has made it necessary for educators to develop new teaching strategies, particularly in the area of questioning techniques. This study aimed to explore the types of questioning strategies employed by teachers during online reading classes and identify the factors that contribute to the frequent use of a specific approach. The study used observation checklists and interview guidelines based on Bloom's taxonomy and Wragg and Brown's questioning strategies to gather data from second-year English language students enrolled in an online reading class. The research findings revealed that to engage students, evaluate their comprehension, and ensure alignment with the textbook material the teacher primarily utilized "Understand" and "Analyze" questions, along with directed, distributed, responded, and sequenced strategies. The teacher also utilized Zoom's chat box feature to ask questions and enable students to provide direct answers. The results of this study demonstrate the importance of effective questioning techniques in online learning environments. The teacher's use of a variety of questioning strategies had a positive impact on the students' ability to acquire knowledge, demonstrating that a diverse range of strategies can help students achieve deeper levels of understanding. The research findings have important implications for the education sector as it provides insights into effective teaching strategies that can help promote student engagement and enhance their learning outcomes.